Adolescent Posyandu Visits, Diet, Nutritional Status, and Anemia in Penatarsewu: Kunjungan Posyandu Remaja, Pola Makan, Status Gizi, dan Anemia di Penatarsewu - Khotimah, Devi Husnul; Cholifah, Cholifah; Rosyidah, Rafhani; Hanum, Sri Mukhodim Faridah (Universitas Muhammadiyah Sidoarjo, 2025)
Background : In Sidoarjo, anemia prevalence among adolescent girls increased from 32.9% in 2020 to 51.6% in 2023, raising concerns about nutrition and preventive health service utilization.Knowledge gap: Although diet, nutritional status, and adolescent Posyandu visits are considered determinants of anemia, the consistency of their relationship is unclear.Aim: This study investigated the relationship between adolescent Posyandu visits, diet, and nutritional status with anemia incidence in Penatarsewu Village.Results: Using a cross-sectional design with total sampling of 32 respondents, hemoglobin levels, BMI, and dietary patterns were assessed. Fisher’s exact test showed no significant relationship between Posyandu visits (p=0.338), diet (p=0.581), or nutritional status (p=0.198) with anemia incidence.Novelty: Unlike many prior studies linking nutrition to anemia, this study reveals that these factors may not directly correlate with anemia in this population.Implications: Other variables, including menstruation, chronic illness, socioeconomic, and environmental factors, should be explored in future studies with larger samples to strengthen anemia prevention strategies. Highlights: Adolescent anemia remains high in Sidoarjo. No significant link between diet, nutrition, visits, and anemia. Broader factors must be considered for anemia prevention. Keywords: Anemia, Adolescent Girls, Posyandu Visits, Diet, Nutritional Status